Morpho-syntaxe sémantique des nominaux propres - Manon Philippe (Corela, 2023)
This paper analyses the morphosyntactic boundaries of proper names in English from the standpoint of the semantics of syntax (form-meaning relations). Typographic, morphological and syntactic properties of proper names are found to be iconically connected and lead to a renewed description of proper names as nominals – rather than simple nouns or noun phrases, as traditional descriptions would have them be. Proper nominals (proper names as syntactic nominals) integrate potentially marginal units into the nominal domain via a twofold process: 1) they showcase their formal and linguistic singularity while 2) imitating the morphosyntactic behaviour of common nouns. This analysis relies on the English common corpus, though examples from the French corpus are also used as most of the analysis remains valid in the French language.